Evaluation of borhani prepared from whole milk, skim milk and full cream powdered milk curd (Asian-Australasian Journal of Food Safety and Security, 2020)
The present research work was carried out to evaluate the qualities of borhani prepared by curd using whole milk, skim milk and full cream powder milk. In this purposes, three types of borhani were prepared, these were grouped as; A: Borhani prepared from whole milk curd, B: Borhani prepared from skim milk curd and C: Borhani prepared from full cream powder milk curd. The prepared borhani samples were subjected to organoleptic, chemical and microbiological qualities. After performed physical examination, for sample A it was found that there was no significant difference in color and appearance (17.67±0.33) but there was significant difference (p